Assessment of Prevalence and Risk Factors of Infertility among Saudi Women: A Cross Sectional Study - Amnah Alghamdi; Nesren Bahnsawy; Nagwa Afefy; Amel Dawod Kamel Gouda (GLOBAL HEALTH SCIENCE GROUP, 2023)
Infertility is a global problem affecting women worldwide. Identifying factors influencing female infertility can help women get successful pregnancies and prevent secondary infertility. The aim of the current study to identify types and assess risk factors of infertility among Saudi women in Riyadh city. A descriptive cross sectional correlational study design was utilized.The researcher developed a questionnaire that comprised of four parts: demographic data, obstetric and gynecological history, medical history, and family history. The data was collected from the patient's medical records using the hospital's BEST care system. The mean age of women was 34.03+ 1.37 years old and half of them 50.4% had a BMI was classified as overweight. Two-third of the women 67.0% had secondary infertility, while one- third 33.0% had primary infertility. Implicated causes among subjects include defect in ovulation was 28.9%, tubal adhesion or obstruction was 7.4%, and male factors was12.6%. There was a statistically significant relationship between types of infertility with age and marital duration,contraceptive methods, duration of contraception used ,causes of infertility and types of drugs for induction of ovulation. Maternal factors as defects in ovulation, tubal adhesion or obstruction, uterine fibroid, pelvic inflammation disease, endometriosis and urinary tract infection and male factors were expressed to be causing infertility. There were risk factors associated with infertility, such as mother age, medical problems, and the types of drugs used to induce ovulation.